Literature Review : The Effect of Forensic Audit, Internal Control, Whistleblowing System, Good Corporate Governance, and Organizational Culture on Fraud Prevention - Azwan Bastian; Hasbiyana Haudi Nasution; Aji Haviz; Handriyani Dwilita (International Journal of Economics, Management and Accounting, 2025)
Focus study This is how forensic audits , internal control , whistleblowing systems , good corporate governance (GCG), and culture organization have an impact on fraud prevention in a organization . Fraud is problem big that can cause loss financial big and destructive reputation company . Research this , based on review comprehensive literature , finding​ that forensic audits are very helpful prevent fraud . Forensic audit use the intended technique For detect fraud . Good internal controls are also important. For build a system that can supervise and manage source Power organization with good , reduce possibility fraud . In addition , the whistleblowing system is considered as tool important For prevent fraud because allows people to report Allegation violation without worry will consequence negative . The study also found that culture strong organization​ can help prevent fraud with create environment work that is moral and transparent . Many studies show that positive culture​ can increase awareness and compliance to policy fraud prevention . As a result , research This suggest that the organization minimize fraud risk with implementing forensic audits , strong internal controls , and a culture of good organization . The result will become more organization​ healthy , transparent and accountable .